Oxidative cracking of aromatic compounds related to lignin constituents with steam using ZrO2-Al2O3-FeOx catalyst - Yoshikawa, Takuya; Na-Ranong, Duangkamol; Tago, Teruoki; Masuda, Takao (My University, 2010)
The catalytic activity of iron oxide composite catalyst (ZrO 2-Al2O3-FeOx) was investigated for converting aromatic compounds derived from plant biomass into useful aromatics. Catalytic cracking of lignin constituent-related di-aroatics such as diphenyl ether, diphenyl methane, and 2-benzyloxyphenol, and mono-aromatics such as guaiacol, acetophenone, and 1-phenyl-1-propanol was carried out over ZrO 2-Al2O3-FeOx. The catalytic reactions were conducted in a fixed-bed reactor at 773 K under atmospheric pressure. Diphenyl ether and diphenyl methane were stable, whereas 2-benzyloxyphenol was thermally decomposed, followed by the production of toluene and phenol over ZrO2-Al2O3-FeO x. Guaiacol and acetophenone were selectively converted into 54 C-mol% of phenol and 29 C-mol% of benzene, respectively. The methoxy and carbonyl groups were decomposed into gaseous products mainly consisting of CO2, whereas dehydration of the aliphatic hydroxyl group in 1-phenyl-1-propanol mainly occurred to produce 1-phenyl-1-propene. ZrO 2-Al2O3-FeOx catalyst is effective for degrading alkyl ether bonds between aromatic rings, and the ring substituent methoxy and carbonyl groups.
Keywords: Biomass; Iron oxide catalyst; Lignin-constituent aromatic; Oxidative cracking; Phenol